BIODIESEL AND BIOETHANOL, FUEL FOR TRANSPORTATION - suharta, herliyani (Agency for the Assessment and Application of Technology)
This paper describes the importance of substituting the fossil fuel for transportation, the existing production of bioethanol and the national target to substitute gasoline until 2025. Specific energy density of biofuel, the properties of jatropha curcas oil and petro-diesel oil are shown to give a sense to compare their energy content. International standard and national standard are also given. The advantage of using biodiesel blend and bioethanol blend for human health and for the environment are described. SVO usage for diesel cars and the conversion equipment needed is described. The use of SVO instead of biodiesel should be considered based on technological and economical point of view to weight the risk. Vision of shifting to biofuel infrastructure the research needed are described. In order to achieve the national target, the tax incentives for fuel efficient cars are given as an example to be considered.